Reproductive performance of White Fulani cows - Aganga, A.A.; Oyejola, B.A.; Aganga, A.O.; Yaakugh, I.D.I. (1986)
Analyses reproductive parameters of White Fulani cows under semi-intensive management in Zaria, Nigeria. Data on age at first service, age at first calving, calving intervals and birth weight included.